Evolving Trends in Pediatric Inflammatory Bowel Disease Management in Japan: A Decade of Nationwide Data - Miki Urushiyama; Kunio Tarasawa; Rintaro Moroi; Hideya Iwaki; Yusuke Hoshi; Hiroshi Nagai; Yusuke Shimoyama; Takeo Naito; Fumihiko Kakuta; Hisashi Shiga; Shin Hamada; Yoichi Kakuta; et al. (JGH Open)
ABSTRACT Aims This study aimed to investigate the trends in pediatric inflammatory bowel diseases (IBD) management in Japan over the past decade. Methods We retrospectively analyzed data from Japan's nationwide database from 2012 to 2022. Patients aged ≤ 15 years diagnosed with Crohn's disease (CD) or ulcerative colitis (UC) were included. Trends in the use of biologics, capsule endoscopy, total parenteral nutrition (TPN), elemental diets, surgery, and granulocyte and monocyte apheresis (GMA) were examined using the Cochrane–Armitage and Jonckheere–Terpstra trend tests. Results Among the 8037 and 6153 pediatric UC and CD admissions, respectively, the use of biologics increased significantly (CD: from 46.0% to 53.6%; UC: from 15.0% to 33.0%, p < 0.0001). The use of capsule endoscopy in pediatric patients with CD increased markedly from 6.6% to 16.7% (p < 0.0001), whereas TPN use decreased from 8.4% to 3.0% (p < 0.0001). Surgery rates for patients with CD remained at approximately 5%, whereas those for patients with UC decreased (from 3.7% to 1.7%, p = 0.002). Elemental diets for pediatric patients with CD increased (from 54.4% to 66.2%, p < 0.0001). The use of GMA decreased significantly in patients with UC (from 12.1% to 2.7%, p < 0.0001). Conclusion The use of biologics and capsule endoscopy has increased in pediatric patients with IBD, whereas the use of more invasive treatments has decreased. These trends suggest a shift toward less invasive and more targeted therapeutic strategies in managing pediatric patients with IBD in Japan.